Effect of Glutamine Before Gets Cisplatin on Aif and Bcl-2 in the Evidence of Apoptosis Cell Tubulus Proximal in Rats Kidney of Rattus Norvegicus Strain Wistar (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Increased incidence of cancer in the world also increases the use of chemotherapy agents. Cisplatin is one of the most effective chemotherapy agents, often used for the treatment of various solid tumors. The therapeutic effect of cisplatin significantly increased with increasing dosage. Aim: The aim of the study was to investigate the role of glutamine in the prevention of apoptosis in proximal renal tubular epithelial cells administered by cisplatin chemotherapy, via an intrinsic caspase-independent apoptotic (AIF). Methods: The study was enrolled thirty male Wistar rats. The rats were divided into three groups of treatments, group A (negative control), group B has given intraperitoneal cisplatin dose of 20 mg/KgBB, group C administered the intravenous injection of glutamine 100 mg/KgBB for 7 days. Results: Analyzed ANOVA, mean expression of BCL-2 group B = 56.80 ± 4.39 than group A (control) = 63.7 ± 5.53 decreased not significant (p = 0.06), and mean expression of BCL-2 group C = 113.30 ± 8.92 increase significant compared to group A = 63.7 ± 5.53 (p = 0.000001) and group B = 56.80 ± 4.39 (p = 0.000001). The average AIF expression group C = 236.20 ± 17.58 decreased significantly compared to group B = 309.50 ± 8.08 (p = 0.000001). The average number of group apoptosis C = 151.80 ± 21.87 decreased significantly compared to group B = 255.20 ± 27.82 (p = 0.000001). Conclusion: Glutamine can inhibit the expression of AIF, increase BCL-2 expression, and decrease apoptosis of epithelial cells of the renal proximal tubules given cisplatin.